Health and Wellbeing in Higher Education: A Comparison of Music and Sport Students Through the Framework of Self Determination Theory - Alessandri, Elena; Rose, Dawn; Wasley, David (Frontiers in Psychology, 2020)
Students in Higher Education report high levels of mental health issues and psychological distress. Paradoxical findings on performance-orientated students, such as athletes and musicians, suggest that the demands of highly skilled vocations may enhance wellbeing while being detrimental to physical and mental health. To provide timely and appropriate help, institutions need to understand what areas of health and wellbeing are compromised in different student groups. In this study, we compared performance-orientated (music, sport) students to other students and the general population on a selection of wellbeing (WHO5, PWS, WEMWBS), mental and physical health (K10, SF12, PHQ9), and trait measures (TIPI, LOT-R, PCS). Through an online survey (N=273), data were collected from bachelor and master students (n=135 music, n=67 sport, n=71 controls). Students’ scores were compared to the general population, where norm values were available, and analysed within and between groups. Multiple regression was performed to investigate trait measures as predictors of wellbeing. All groups scored significantly below population norms for wellbeing and mental health. One third were classed as having moderate to severe depression. Athletes scored lower pessimism; musicians higher openness to experience than the other groups. While sport students showed a highly homogenous within-group profile, music students’ scores differed significantly across study courses (e.g. performance, composition). Predictors for wellbeing were: optimism and emotional stability (all students); additionally conscientiousness (sport and music); and perceived competence (music only). As expected, students reported more health and wellbeing issues than general population. Distinct profiles of wellbeing were apparent for performance-orientated students. Results are in line with Self Determination Theory and suggest the need for institutions to embed health and wellbeing into a ‘living curriculum’ to accommodate the needs of different student groups. The WHO5 emerged as a parsimonious yet sensitive measure for mental health and wellbeing in student populations.